Sailors and Traders A Maritime History of the Pacific Peoples - Couper, Alastair (University of Hawai'i Press, 2020)
Written by a senior scholar and master mariner, Sailors and Traders is the first comprehensive account of the maritime peoples of the Pacific. It focuses on the sailors who led the exploration and settlement of the islands and New Zealand and their seagoing descendants, providing along the way new material and unique observations on traditional and commercial seagoing against the background of major periods in Pacific history. The book begins by detailing the traditions of sailors, a group whose way of life sets them apart. Like all others who live and work at sea, Pacific mariners face the challenges of an often harsh environment, endure separation from their families for months at a time, revere their vessels, and share a singular attitude to risk and death.The period of prehistoric seafaring is discussed using archaeological data, interpretations from inter island exchanges, experimental voyaging, and recent DNA analysis. Sections on the arrival of foreign exploring ships centuries later concentrate on relations between visiting sailors and maritime communities. The more intrusive influx of commercial trading and whaling ships brought new technology, weapons, and differences in the ethics of trade. The successes and failures of Polynesian chiefs who entered trading with European-type ships are recounted as neglected aspects of Pacific history. As foreign-owned commercial ships expanded in the region so did colonialism, which was accompanied by an increase in the number of sailors from metropolitan countries and a decrease in the employment of Pacific islanders on foreign ships. Eventually small-scale island entrepreneurs expanded inter island shipping, and in 1978 the regional Pacific Forum Line was created by newly independent states. This was welcomed as a symbolic return to indigenous Pacific ocean linkages.The book's final sections detail the life of the modern Pacific seafarer. Most Pacific sailors in the global maritime labor market return home after many months at sea, bringing money, goods, a wider perspective of the world, and sometimes new diseases. Each of these impacts is analyzed, particularly in the case of Kiribati, a major supplier of labor to foreign ships.